Self-traceable angle standards with simplified traceability chain for dimensional metrology - Xiao Deng; Junyu Shen; Yingfan Xiong; Jinming Gou; Zhaohui Tang; Guangxu Xiao; Zhijun Yin; Dongbai Xue; Yushu Shi; Zhoumiao Shi; Yuying Xie; Xinbin Cheng; et al. (Applied Physics Express)
Traceability is a fundamental issue for ensuring accuracy of nanometrology. A shortened traceability chain is advantageous for reducing calibration steps, thus reducing errors and raising application efficiency. A novel kind of two-dimensional grating is manufactured by atom lithography, whose pitch and (orthogonal) angle values are directly determined by natural constants, offering a feasible approach for effectively shortening the traceability chain. The PTB’s calibration results show that the two-dimensional grating has excellent orthogonality with a deviation of only 0.001°. The application of two-dimensional grating is demonstrated for the characterization of the angular distortion of a SEM, showing its great application potential.